Pengaruh Produk, Harga, Promosi dan Distribusi Terhadap Keputusan Pembelian Pada UMKM Keripik Singkong Sabar Menanti Di Kabupaten Sumenep - sofiyana, vita; Syarif, Muh (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
This study aims to determine the effect of product, price, promotion and distribution on purchasing decisions in UMKM Sabar Menanti Chips in Sumenep District. The research method used in this research in quantitative method. This research technique used purposive sampling with a total sampleof 97 respondents. For data collection instruments used in the form of questionnaires distributed to consumers who have bought sabar menanti chips patiently waiting. The independent variables in this study are product, price, promotion and distribution, while the dependent variable is the purchase decision.